Mamld1 knockdown reduces testosterone production and Cyp17a1 expression in mouse Leydig tumor cells. - Michiko Nakamura; Maki Fukami; Fumihiro Sugawa; Mami Miyado; Katsuya Nonomura; Tsutomu Ogata (PLoS ONE, 2011)
MAMLD1 is known to be a causative gene for hypospadias. Although previous studies have indicated that MAMLD1 mutations result in hypospadias primarily because of compromised testosterone production around the critical period for fetal sex development, the underlying mechanism(s) remains to be clarified. Furthermore, although functional studies have indicated a transactivation function of MAMLD1 for the non-canonical Notch target Hes3, its relevance to testosterone production remains unknown. To examine these matters, we performed Mamld1 knockdown experiments.Mamld1 knockdown was performed with two siRNAs, using mouse Leydig tumor cells (MLTCs). Mamld1 knockdown did not influence the concentrations of pregnenolone and progesterone but significantly reduced those of 17-OH pregnenolone, 17-OH progesterone, dehydroepiandrosterone, androstenedione, and testosterone in the culture media. Furthermore, Mamld1 knockdown significantly decreased Cyp17a1 expression, but did not affect expressions of other genes involved in testosterone biosynthesis as well as in insulin-like 3 production. Hes3 expression was not significantly altered. In addition, while 47 genes were significantly up-regulated (fold change >2.0×) and 38 genes were significantly down-regulated (fold change <0.5×), none of them was known to be involved in testosterone production. Cell proliferation analysis revealed no evidence for compromised proliferation of siRNA-transfected MLTCs.The results, in conjunction with the previous data, imply that Mamld1 enhances Cyp17a1 expression primarily in Leydig cells and permit to produce a sufficient amount of testosterone for male sex development, independently of the Hes3-related non-canonical Notch signaling.